The Metabolic Syndrome among Postmenopausal Women in Gorgan - Abdoljalal Marjani; Sedigheh Moghasemi (International Journal of Endocrinology)
Introduction. The present study aimed to assess the metabolic syndrome among postmenopausal women in Gorgan, Iran. Materials and Methods. The study was conducted on hundred postmenopausal women who were referred to the health centers in Gorgan. Metabolic syndrome was diagnosed using Adult Treatment Panel III (ATP III) guidelines. Results. The mean body mass index, waist circumference, hip, circumference waist-to-hip ratio, diastolic blood pressure, and triglyceride and fasting blood glucose levels were significantly high among postmenopausal women with metabolic syndrome, but the mean HDL-cholesterol was significantly low (P<0.05). Overall prevalence of metabolic syndrome was 31%. Body mass index and waist circumference had a positive correlation with a number of metabolic syndrome factors (P<0.001). Body mass index, waist circumference, and waist-to-hip ratio had a positive correlation with each other (P<0.001). BMI had relatively high correlation with WC (P<0.001). Conclusions. Our results show that postmenopausal status might be a predictor of metabolic syndrome. Low HDL-cholesterol level and high abdominal obesity are the most frequent characteristics in comparison to other metabolic components. Our study also showed some related factors of metabolic syndrome among postmenopausal women. These factors may increase cardiovascular risk among postmenopausal women with metabolic syndrome.